Mechanistic and phylogenetic insights into actinobacteria‐mediated oestrogen biodegradation in urban estuarine sediments - Hsiao, Tsun‐Hsien; Chen, Yi‐Lung; Meng, Menghsiao; Chuang, Meng‐Rong; Horinouchi, Masae; Hayashi, Toshiaki; Wang, Po‐Hsiang; Chiang, Yin‐Ru (Microbial biotechnology, 2021)
Summary Steroidal oestrogens are often accumulated in urban estuarine sediments worldwide at microgram per gram levels. These aromatic steroids have been classified as endocrine disruptors and group 1 carcinogens. Microbial degradation is a naturally occurring mechanism that mineralizes oestrogens in the biosphere; however, the corresponding genes in oestrogen‐degrading actinobacteria remain unidentified. In this study, we identified a gene cluster encoding several putative oestrogen‐degrading genes (aed; actinobacterial oestrogen degradation) in actinobacterium Rhodococcus sp. strain B50. Among them, the aedA and aedB genes involved in oestrogenic A‐ring cleavage were identified through gene‐disruption experiments. We demonstrated that actinobacterial oestrone 4‐hydroxylase (AedA) is a cytochrome P450‐type monooxygenase. We also detected the accumulation of two extracellular oestrogenic metabolites, including pyridinestrone acid (PEA) and 3aα‐H‐4α(3'‐propanoate)‐7aβ‐methylhexahydro‐1,5‐indanedione (HIP), in the oestrone‐fed strain B50 cultures. Since actinobacterial aedB and proteobacterial edcB shared < 40% sequence identity, 4‐hydroxyestrone 4,5‐dioxygenase genes (namely aedB and edcB) could serve as a specific biomarker to differentiate the contribution of actinobacteria and proteobacteria in environmental oestrogen degradation. Therefore, 4‐hydroxyestrone 4,5‐dioxygenase genes and the extracellular metabolites PEA and HIP were used as biomarkers to investigate oestrogen biodegradation in an urban estuarine sediment. Interestingly, our data suggested that actinobacteria are active oestrogen degraders in the urban estuarine sediment. We identified a gene cluster encoding several putative estrogen‐degrading genes (aed; actinobacterial estrogen degradation) in actinobacterium Rhodococcus sp. strain B50. Among them, the aedA and aedB genes involved in estrogenic A‐ring cleavage were identified through gene‐disruption experiments.